The changing landscape of nuclear medicine and a new era: the “NEW (Nu) CLEAR Medicine”: a framework for the future - Djekidel, Mehdi (Frontiers in Nuclear Medicine, 2023)
Nuclear Medicine is witnessing a revolution across a large spectrum of patient care applications, hardware, software and novel radiopharmaceuticals. We propose to offer a framework of the nuclear medicine practice of the future that incorporates multiple novelties and coined as the NEW (nu) Clear medicine. All these new developments offer a significant clarity and real clinical impact, and we need a concerted effort from all stakeholders in the field for bedside implementation and success.